Uterine fibroid: size does matter - Marques,Mariana Crespo (2022)
Abstract Leiomyomas are the most common benign tumors in reproductive age women. The incidence is higher in African descent women. Development and growth of fibroids is estrogen and progesterone dependent. Besides excessive menstrual bleeding, pelvic pain is also a common symptom. Doppler ultrasound (dUS) or magnetic resonance imaging (MRI) are useful for preoperative differentiation between benign and the more uncommon malignant forms. Treatment of leiomyomas depends on size, location, severity of symptoms and patient desire to preserve fertility. The authors present a case of a 16 cm subserous cervical myoma that occupied the pelvic cavity. Laparotomy was performed for tumor excision.